Determination of Mango Fruit Maturity on the Tree Based on Digital Image Processing and Artificial Neural Networks - Aditia Sanjaya; Ichwanul Muslim Karo Karo (Journal of Software Engineering, Information and Communication Technology (SEICT), 2023)
Until now, humans have determined the ripeness of mangoes on the tree by hand. Losses are caused by the insecurity of the human state and a misunderstanding of the maturity level of mangoes. In the future, a system that can detect the ripeness of mangoes on the tree will be required. This research provides a preliminary examination of the technology's implementation. The study created a computerized image processing method for determining the ripeness of mangoes on the tree. The neural network backpropagation algorithm was employed in this investigation. The feature extraction model employed in the image is a hybrid of the RBG and HSV models. The best accuracy level is 72%, with an 80:20 ratio of test data to training data.